The ESCRT-0 component HRS is required for HIV-1 Vpu-mediated BST-2/tetherin down-regulation. - Katy Janvier; Annegret Pelchen-Matthews; Jean-Baptiste Renaud; Marina Caillet; Mark Marsh; Clarisse Berlioz-Torrent (PLoS Pathogens)
The Endosomal Sorting Complexes Required for Transport (ESCRT) machinery, a highly conserved set of four hetero-oligomeric protein complexes, is required for multivesicular body formation, sorting ubiquitinylated membrane proteins for lysosomal degradation, cytokinesis and the final stages of assembly of a number of enveloped viruses, including the human immunodeficiency viruses. Here, we show an additional role for the ESCRT machinery in HIV-1 release. BST-2/tetherin is a restriction factor that impedes HIV release by tethering mature virus particles to the plasma membrane. We found that HRS, a key component of the ESCRT-0 complex, promotes efficient release of HIV-1 and that siRNA-mediated HRS depletion induces a BST-2/tetherin phenotype. This activity is related to the ability of the HIV-1 Vpu protein to down-regulate BST-2/tetherin. We found that BST-2/tetherin undergoes constitutive ESCRT-dependent sorting for lysosomal degradation and that this degradation is enhanced by Vpu expression. We demonstrate that Vpu-mediated BST-2/tetherin down-modulation and degradation require HRS (ESCRT-0) function and that knock down of HRS increases cellular levels of BST-2/tetherin and restricts virus release. Furthermore, HRS co-precipitates with Vpu and BST-2. Our results provide further insight into the mechanism by which Vpu counteracts BST-2/tetherin and promotes HIV-1 dissemination, and they highlight an additional role for the ESCRT machinery in virus release.